Root-rhizosphere interactions and modifications - Lapsansky, Erin Rebecca, author; Vivanco, Jorge M., advisor; Stromberger, Mary, committee member; Pilon-Smits, Elizabeth, committee member; Wallner, Stephen, committee member (Colorado State University. Libraries, 2016)
The interactions between the plant and rhizosphere are complex, but recent research is elucidating more about a diverse array of relationships. In response to the growing demand for natural or plant produced pesticides and herbicides, a novel method for the identification of bioactive root exudates was developed utilizing the hypothesis that exudate compounds changing in relative abundance over plant development were likely bioactive. Research investigated this hypothesis on Arabidopsis grown in vitro and then in maize grown under greenhouse conditions. Four compounds were identified as bioactive, modifying plant growth, supporting this novel method of bioactive compound identification. In a second study, it was hypothesized that Plant Growth Promoting Rhizobacteria (PGPR) could be used to induce specific changes to Root System Architecture (RSA) which could impart growth benefits in specific environmental conditions. In vitro, three bacterial strains displayed the ability to modify RSA, and in a greenhouse study with nutrient deficiency, one strain was able to impart growth benefit to Arabidospsis. Both bioactive root exudates and PGPR demonstrated the potential to create desired root morphology, suggesting that root systems could be optimized to overcome environmental limitations such as drought or nutrient deficiency. Finally, a review focusing on a novel interpretation of the relationship between plants and the rhizosphere, discusses how the plant primes the rhizosphere to support and protect its offspring.